UPAYA LEMBAGA PENJAMIN SIMPANAN DALAM MENGATASI PENYELESAIAN DAN PENANGANAN FAILING BANK - Raras Putri Weda, Ni Made; Sukranatha, Anak Agung Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014, 2014)
This paper shall be emtitled as Deposit Insurance Agenncy (LPS) Intiatives in Setting Failing Banks. In its composition, this writing shall apply normative legal research by investigating principles of law, systems of law, and law hormonization degree. LPS shall be positioned as independent body which is assigned to insure the deposit of the customer and also to actively anganging the banking system stability, one of itshall be the sentlement of the failing bank. Hence, this writing shall illustrate is general manner, concerning failing bank and LPS procedure in setting the failing bank.
Keywords: Deposit Insurance Agenncy, Failing Bank, Banking